Analisis Penentuan Waktu Standar Operasi Pemboran dan Produktivitas Jumbo Drill pada Pembuatan Lubang Ledak Menggunakan Metode Analisa Elemen Kerja dan Waktu Baku di Tambang Emas Bawah Tanah PT. Cibaliung Sumberdaya, Kabupaten Pandagelang, Provinsi Banten - Jevindo Ornandi Gemvita; Mulya Gusman (Journals Mining Engineering : Bina Tambang, 2020)
Abstract. PT Cibaliung Sumberdaya is a gold mining company that implements an underground mining system. PT Cibaliung Sumberdaya is a subsidiary of PT. Aneka Tambang (Antam) located in Cimanggu District, Pandegelang Regency, Banten Province. In the production activities, the drill tool used for the activity is the Atlas Copco Boomer 282 with R32 drilling bit diameter 43 mm for drilling holes for split sets in supporting mesh and 51 mm diameter for explosive hole drilling using rotary-percussive drilling methods and burn cut drilling patterns . In August 2019 PT. CSD 14,397.6 wmt / month and actually reached 12,893.4 wmt / month. Based on the calculation, the actual productivity of the calculation results obtained 18.29 wmt / hour or 164.56 wmt / day which after the reduction of the tool productivity increased from 164.56 wmt / hour to 246.85 wmt / day. The Standard Time obtained from the calculation results is in the Drill Face Drilling of Class IV Rocks = 6.21 Minutes and Class III Rocks = 6.66 Minutes. On the Hole Drilling for Split Set and Wiremesh Installation the Class IV Rocks in Hole Drilling for Split Set = 5.87 Minutes and Wiremesh Installation = 7.39 Minutes, while those for Class III Rock in Hole Drilling for Split Set = 5.65 Minutes and Wiremesh Installation = 5.35 MinutesKeywords: Jumbo Drill, Productivity, Drill Face, Supporting, The Standard Time